Penerapan BIM dalam Perhitungan Volume Pekerjaan dan Biaya Konstruksi Menggunakan Software Autodesk Revit pada Proyek Gedung Pengadilan Agama Sungai Raya - Muhammad Naufal Habibbullah; Lusiana Lusiana; Rafie Rafie (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The calculation of work volume and construction costs is a fundamental aspect of project management, as errors in the estimation process can directly affect the preparation of the project budget. Many projects still use conventional methods for estimation, which are based on 2D working drawings with the assistance of Microsoft Excel, as seen in the Sungai Raya Religious Court Building project. This method is considered prone to calculation errors and less efficient due to the considerable amount of time required. With the advancement of technology, Building Information Modeling (BIM) has emerged, enabling automatic and integrated calculation of work volumes and construction costs through a three-dimensional digital model. This study aims to examine the implementation of BIM in the Sungai Raya Religious Court Building project and to compare the results of work volume and construction cost calculations between the BIM method using Autodesk Revit and the conventional method based on the project’s Bill of Quantity (BoQ). The research method was conducted by modeling the structural elements of the building, including pile caps, tie beams, columns, beams, floor slabs, and reinforcements. The results of work volume and construction cost calculations obtained from Autodesk Revit were then compared with the project’s BoQ as the conventional method. Based on the analysis, an average difference of 6.3% in work volume and 5.6% in construction cost was found, with the Autodesk Revit calculations showing slightly lower values compared to the project’s BoQ.